An Analysis Study of Sunspot Numbers and Solar Radio Flux (10.7 cm) for the Raising Phase of the Solar Cycle 25 - Hassan, Muna A.; Ahmed, Ala F. (Iraqi Journal of Science, 2025)
The present study used the solar radio flux (F10.7 cm) and the sunspot number (SSN) created throughout five years, beginning in December 2019 and ending in December 2023, for the solar cycle 25. The number of sunspots and the solar radio flux were measured monthly using data from the WDC-SILSO, Royal Observatory of Belgium, Brussels. A five-year link between the two variables was constructed, marking the start of the solar cycle 25 (2019 to 2023) years. Understanding their relationship and the degree to which they impact solar activity, which affects terrestrial and space technology, is also important. For sunspots, the highest value reached (127.6) in 2023, while the lowest value (1.8) was attained in 2019. With time, the value increased like the number of spots, rising and falling until it achieved its maximum value over the course of the five years (159.1 radio flux number) in 2023.  Both serve as markers for rising and falling solar activity levels. Through statistical analysis and graphs for each of them that depict the pattern of solar activity for that time period, this study demonstrated the strong, persistent association between the number of sunspots and solar radio flux. Additionally, helpfully, the rising phases of the solar cycles 24 and 25 were compared over the same period, including the first five years. This forecasts what the 25th cycle's supplemental chart will look like for the next five years.